Peningkatan Kecerdasan Spritual Melalui Konsep “Ikhlas Dan Ridha” Atas Pengabdian Kepada Keluarga Guru (Kyai) Pondok Pesantren - Najmi, Akmalun; Habibah, Habibah; Inayati, Mahfida (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
Spiritual intelligence is a limited thing and is not always possessed by every student who serves the kyai. Significant spiritual intelligence in the context of this devotion largely depends on two key elements, namely sincerity and pleasure. That is, only through the purity of intention (sincerity) and acceptance and satisfaction of Allah's destiny (ridha), a person can develop higher spiritual intelligence in his devotion to kyai. These concepts are not only the performance of duties, but also imply a deep inner dimension, which is the main foundation to reach the peak of wisdom and spiritual growth so that in this peelitian it is discussed about the concept of sincerity and pleasure for students who serve the kyai can increase their spiritual intelligence. In this article, the researcher uses a qualitative research method with a mini research object approach. The results of this study show that it is true that students who serve the kyai based on sincerity and pleasure can increase their spiritual intelligence, starting with respect and obedience, a sense of acceptance and willingness to learn, a sense of hope for Allah's pleasure and a sense of developing their spiritual awareness.